The FT IR and laser Raman Spectral Investigation of 4 4 Bipyridily Transition Metal II Tetracyanonickelate Clathrates - Davies, J. Eric D.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Kluwer Academic Publishers, 1996)
The FT-IR and Raman spectra are reported of M(4,4′-bipyridyl)Ni(CN)4·nG (where M = Mn, Fe, Co, Cu or Zn and G = benzene or aniline;n = 0–2) clathrates. The host structure consists of a three-dimensional rigid lattice formed by infinite polymeric layers of {M-Ni(CN)4}∞ and 4,4′-bipyridyl bridges between the metal (M) atoms of the adjacent polymeric layers. Bidentate 4,4′-bipyridyl molecules are found to be centrosymmetric in the structure.
Keywords: Tetracyanonickelate compounds; benzene clathrate; aniline clathrate; IR and Raman spectra; 4,4′-bipyridyl complexes